Óleo de linhaça na dieta de frangos de corte - Lopes, Débora Cristina Nichelle (2012)
A trial was conducted to evaluate the effects of replacing soybean oil by linseed oil on performance, carcass traits, physicochemical characteristics, sensory properties of meat and plasma biochemical profile of poultry. A total of 448 one day old male birds (Cobb 500) where randomly allotted to 4 treatments and 8 replications in a completely randomized assay for 35 days. The following treatments were tested: T1 = 100% soybean oil (SO) as the main dietary energy source; T2 = 50% SO and 50% linseed oil (LO); T3 = 25% SO and 75% LO; and T4 = 100% LO. Performance of birds was not affected (P>0.05) when LO replaced SO in the diets during the whole experimental period. Additionally, no significant difference (P>0.05) was observed in carcass traits of birds fed diets containing LO. Moreover, plasma biochemical profile was not affected (P>0.05) as the level of LO increased in the diets. Omega-3 fatty acids (n3-PUFA) increased in the meat, omega-6 fatty acids (n6-PUFA) and meat n6:n3 decreased as the dietary level of LO was increased. Reduction of drumstick fat was observed increasing levels of LO in the diet (P<0,05). No significant differences (P>0.05) were observed for dry matter, protein, fat and cholesterol in the meat. Also, no significant differences (P>0.05) were found for physicochemical characteristics and sensory properties of meat. Replacing SO by LO in the diet might be carried out with no effect on performance, carcass traits and biochemical profile of poultry. Dietary LO enriched poultry meat with C18:3n3, C20:3n3 e C20:5n3 and reduced n6:n3 ratio without any negative effects on chemical composition and physicochemical characteristics and sensory properties of meat.